Cutting propagation technique of mahogany (Swietenia macrophylla) in microtunnels from the Peruvian Amazon - Vallejos, Geomar; Gaona-Jimenez, Nery; Ordoñez-Sánchez, Luis; García-Gonzales, Patricia; Mendoza-Caballero, Wilfredo; Saavedra-Ramírez, Jorge; Macedo-Córdova, Wilder; Reátegui, Keneth; Baselly-Villanueva, Juan Rodrigo; Marín, Césár (BOSQUE, 2025)
Swietenia macrophylla is a forest species of great commercial value that is categorized as vulnerable in Peru. Therefore, the objective of this study was to optimize a protocol for cutting propagation of S. macrophylla using microtunnels in the San Martín, Peruvian Amazon. Three experiments were conducted: sterilization, which tested ethyl alcohol (EA), Tween-80 (T), carbendazim (CZ), and combinations; a rooting experiment with different substrates and doses of indole-3-butyric acid (IBA); and an acclimation experiment of rooted cuttings, with different shade coverage and relative humidity conditions. The lowest contamination of S. macrophylla cuttings (9.75 %) was achieved with the combined EA-CZ treatment; this treatment resulted in the lowest necrosis (9.1 %) and survival of